ORGANIC TOMATO (Solanum lycopersicum L.) PRODUCTION UNDER DIFFERENT MULCHES IN GREENHOUSE - H. Ozer (Journal of Animal and Plant Sciences, 2017)
Mulching is an important application in greenhouse production. It controls soil moisture, improves soil structure and helps against weeds and diseases. The aim of this study was conducted to determine the effects of different inorganic (B: black, SG: silver gray, R: red and GC: ground cover PE) and organic (S: straw) mulches on earliness, yield and some quality parameters of tomatoes (Solanum lycopersicum, L. cv. Sumela F1) grown under greenhouse conditions in Black Sea Region of Turkey during 2009-2010. In this study, leaf stomatal conductance, leaf chlorophyll content, photosynthesis rates, yield, soluble solids content (SSC), titratable acidity (TA), fruit firmness, vitamin C and phenological traits were examined.  The highest chlorophyll content (43.9 CCI) and firmness (24.5 N) was obtained from silver gray mulch treatments. PE mulch treatments had higher yields (6256.32 kg da-1) than organic mulch and control treatment (C). On the other hand, while the highest soluble solids content (5.4 %) and vitamin C (40.7 mg 100 g-1) contents were obtained from the control treatment, the highest titratable acidity (0.44 %) was obtained from red PE mulch treatment. Significant differences were not observed between the leaf stomal conductance (128.68 mmol m-2s-1) and photosynthesis rates (84.1 µmol O2 m-2s-1) of mulch treatments and control treatment. It was concluded that mulch treatments had significant effects on yield and quality of tomatoes (P≤0.05).
Keywords: Earliness; photosynthesis; stoma; quality; yield